Cationic starch-grafted-cationic polyacrylamide based graphene oxide ternary composite flocculant for the enhanced flocculation of oil sludge suspension. (15th November 2019) - Chen, Ying; Tian, Gongwei; Zhai, Boyin; Zhang, Huili; Liang, Yuning; Liang, Hongbao
Abstract: In this study, a novel, highly efficient and environmentally friendly ternary composites flocculant, namely, cationic starch-grafted-cationic polyacrylamide/graphene oxide (CS-g-CPAM/GO), was synthesized by ammonium persulfate initiation polymerization and condensation reaction. First, CS-g-CPAM was polymerized with cationic starch (CS), acrylamide (AM) and diallyl dimethyl ammonium chloride (DMDAAC), and CS-g-CPAM/GO was then synthesized by condensation reaction. The influence factors of graft polymerization were investigated, including total monomer concentration, initiator dosage, monomer mass ratio of m AM : m CS : m DMDAAC, post-polymerization temperature and post-polymerization time. The chemical structures and morphologies of the samples were characterized by Fourier transform-infrared spectroscopy (FT-IR), X-ray diffraction (XRD), thermo-gravimetric and differential scanning calorimetry (TG-DSC), and scanning electron microscope (SEM). The CS-g-CPAM/GO was used to flocculate the oil sludge suspension, the effects of CS-g-CPAM/GO dosage, temperature and pH value on the flocculation performance were investigated, and the flocculation mechanism of CS-g-CPAM/GO was also analyzed. The results show that CS-g-CPAM/GO has outstanding flocculation effect, and CS-g-CPAM/GO flocculates oil sludge particles by adsorption bridging and charge neutralization in acidic and alkaline conditions. Graphical abstract: Image 1 Highlights: Novel CS-g-CPAM/GO flocculants were synthesized. Chemical structures were characterized and analyzed. Flocculation mechanism were summarized.